Constitutional Framework for Mining Regulation: Regional Autonomy and State Authority - Sumirat, Iin Ratna; Rahman, Arif; Tabrozi, Dhika; Wazin, Wazin (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
The licensing of minerals and coal in Indonesia faces significant challenges, particularly concerning legal certainty and fair intergovernmental relationships. This research delves into the legal uncertainties emerging from the central-regional framework defined by Article 18 of the 1945 Constitution and Law No. 23/2014 on Regional Government. It also examines sectoral regulations as laid out in Law No. 4/2009, amended by Law No. 3/2020 and Law No. 2/2025, and Government Regulation No. 25/2024. Through a normative legal methodology that includes legislative, conceptual, and comparative analyses, the study highlights issues such as: overlapping mandates between laws, unclear operational boundaries between Law No. 23/2014 and post-2020 mining regulations, and inconsistencies in enforcement practices. A significant conclusion of the research emphasizes the constitutional authority given to Regional Governments to regulate and oversee mining operations within their areas. However, the implementation Law No. 2 may unintentionally undermine regional autonomy and modify the crucial role of Regional Governments as primary regulators in the mining sector. Additionally, the assignment of authority to mass organizations and universities in mining management in mining raises serious questions regarding legal hierarchy and compliance with constitutional mandates, potentially conflicting with their official roles and purposes.